Rethinking a Better Life – (Im)mobility Experiences of Vilnius Roma Families - Avin, Agnieška (Vilnius University Open Series, 2025)
Most of the Vilnius Roma families are actively engaged in transnational family networks shaping their everyday life, their social imaginations and life trajectories. When discussing the migratory experiences and the meaning of a better life, there is a constant comparison between ‘here’ and ‘there’, or between lives in Lithuania and abroad. ‘Here’ is a place where Roma are always spotted and stigmatised, while ‘there’ assures invisibility and, hence, more opportunities. The circulating ideals about the ‘abroad’ can be read as a disappointment with a life ‘here’ – what is idealised, fantasised and seen as a goal ‘out there’, it is what people would wish to have in Lithuania. This comparison and lived experiences are becoming a collective community knowledge that is shared among all generations – one does not have to really experience life abroad to know that there is a place where everyone “can feel a human being.” But can the imagined paradise be also criticised and questioned? Can a better life be related only to some geographical space and socio-economic experiences? This chapter is based on a long-term ethnographic fieldwork among Vilnius Roma families.